Shapes of tourism employment : HRM in the worlds of hotels and air transport - e; Peyrat-Guillard, Dominique (London : ISTE Ltd. ; Hoboken : Wiley, 2020)
The ambition of this book is to propose a grid of reading able to illuminate the current HR transformations experienced by the big historical international companies of the sector of the tourism, carried away by what is known as the "3rd tourist revolution ". The latter is characterized by the combination of three main phenomena: internationalization, digitalization and hyper-personalization that refound the employment relationship between employers, unions and employees. Internationalization requires a renewal of business models heckled by the low-cost strategies of new operators provoking social reactions to the extent of perceived psychological disruptions, to question the validity of these same strategies. Digitization has opened the way to the disintermediation at the origin of the evolution of the trades front and back office. Finally, hyper-personalization and adaptation to new client behaviors justify the hegemony of soft skills for a redefined hospitality. In the end, the employee must constantly deal with often paradoxical injunctions (example: standardization of service protocols versus empowerment). A focus will be made on two specific branches: hotels and air transport which will each be part of a part. The topic will be illustrated by case studies and testimonials. The two coordinators of the book will draw on the contributions of researchers who collaborate with them in the framework of an international research program they pilot.
Includes bibliographical references and index.
Online resource, title from digital title page (viewed on March 11, 2021).
John Wiley and Sons
Keywords: Tourism -- Personnel management; Tourism -- Personnel management